2015
DOI: 10.5152/jarem.2015.698
|View full text |Cite
|
Sign up to set email alerts
|

The Reflux Finding Score: Reliability and Correlation to the Reflux Symptom Index

Abstract: Objective: To evaluate the correlation between the reflux symptom index (RSI) and the reflux finding score (RFS) in the patients with voice-related problems and to investigate the reliability of RFS.Methods: Fifty-four patients presenting with the complaint of voice abnormality were included in the study. Patients were asked to complete an RSI score sheet, and they were examined by rigid laryngostroboscopy. Laryngostroboscopic examinations of the patients were evaluated and rated with RFS by three different ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…5 Karakaya et al also demonstrated high intra rater and inter rater reliability for RFS score; findings of Vocal fold edema and the thick endolaryngeal mucus showed highest intra rater and inter rater agreement. 6 Study by Branski et al noted relatively poor inter and intra rater agreement for the variables of the laryngeal findings. 7 Only finding of edema of the musculo membranous fold exhibited fair reliability.…”
Section: Resultsmentioning
confidence: 96%
“…5 Karakaya et al also demonstrated high intra rater and inter rater reliability for RFS score; findings of Vocal fold edema and the thick endolaryngeal mucus showed highest intra rater and inter rater agreement. 6 Study by Branski et al noted relatively poor inter and intra rater agreement for the variables of the laryngeal findings. 7 Only finding of edema of the musculo membranous fold exhibited fair reliability.…”
Section: Resultsmentioning
confidence: 96%
“…Research into early detection and diagnosis of LPRD with a simple, economical and non invasive instrument led Belfasky et al to develop the RFS an 8-item, validated, reliable, easily administered clinical severity scale used to interpret the most common laryngoscopic findings related to LPRD. As subtle findings of LPRD are present in most individuals, RFS [ 7 indicates that the patient has LPRD with 95% certainty [16,17], and is thus a part of the standard diagnostic protocol for patients with dysphonia in our Department. Twenty-four-hour ambulatory dual-probe pH monitoring is currently the gold standard for the objective diagnosis of LPRD [16].…”
Section: Discussionmentioning
confidence: 99%
“…As subtle findings of LPRD are present in most individuals, RFS [ 7 indicates that the patient has LPRD with 95% certainty [16,17], and is thus a part of the standard diagnostic protocol for patients with dysphonia in our Department. Twenty-four-hour ambulatory dual-probe pH monitoring is currently the gold standard for the objective diagnosis of LPRD [16]. Multichannel intraluminal impedance measurement has been added to pH monitoring (MII-pH) and may improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPR is a big problem for public health because of its high incidence, which is about 10% of all patients who come to the ENT doctor's practice. 1,5,6 Previous studies reported that risk factors for age, sex, BMI, smoking history and diet determine the severity of LPR, which can lead to mental problems in patients. Duration of symptoms may be a risk factor because it can aggravate LPR.…”
Section: Introductionmentioning
confidence: 99%